Management of Conflicts of Interest in WHO's Consultative Processes on Global Alcohol Policy - June YY Leung; Sally Casswell (Kerman University of Medical Sciences, 2022)
Background  The World Health Organization (WHO) has engaged in consultations with the alcohol industry in global alcohol policy development, including currently a draft action plan to strengthen implementation of the Global strategy to reduce the harmful use of alcohol. WHO's Framework for Engagement with Non-State Actors (FENSA) is an organization-wide policy that aims to manage potential conflicts of interest in WHO's interactions with private sector entities, non-governmental institutions, philanthropic foundations and academic institutions. Methods  We analysed the alignment of WHO's consultative processes with non-state actors on "the way forward" for alcohol policy and a global alcohol action plan with FENSA. We referred to publicly accessible WHO documents, including the Alcohol, Drugs and Addictive Behaviours Unit website, records of relevant meetings, and other documents relevant to FENSA. We documented submissions to two web-based consultations held in 2019 and 2020 by type of organization and links to the alcohol industry. Results  WHO's processes to conduct due diligence, risk assessment and risk management as required by FENSA appeared to be inadequate. Limited information was published on non-state actors, primarily the alcohol industry, that participated in the consultations, including their potential conflicts of interest. No minutes were published for WHO's virtual meeting with the alcohol industry, suggesting a lack of transparency. Organizations with known links to the tobacco industry participated in both web-based consultations, despite FENSA's principle of non-engagement with tobacco industry actors. Conclusion  WHO's consultative processes have not been adequate to address conflicts of interest in relation to the alcohol industry, violating the principles of FENSA. Member states must ensure that WHO has the resources to implement and is held accountable for appropriate and consistent safeguards against industry interference in the development of global alcohol policy.